2018
DOI: 10.1111/ics.12465
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fatty acid methyl esters in cosmetic castor oils by flow injection–electrospray ionization–high‐resolution mass spectrometry

Abstract: Objective The goal of this work was to set up a high throughput procedure for the determination of fatty acid methyl esters (FAMEs) in cosmetic castor oils using flow injection–electrospray ionization–high‐resolution mass spectrometry, and to demonstrate the need of such analysis for the quality control purposes. Methods The sample aliquot was mixed with isooctane:chloroform (1:1) and submitted to transesterification; the obtained FAMEs were appropriately diluted using water:isopropanol:acetonitrile (20:50:30)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The difference could also be related to varied anionic head group contributions with the sodium sulfonate group in SEFAMESO contributing 11 and sodium sulfate in SDS contributing 38.7 . The HLB value of SEFAMESO suggested that the synthesized surfactant is potentially suitable for use as a wetting or solubilizing agent in the formulation of shampoos. , Studies have also shown that mixed surfactant systems derived from edible oleochemical fatty methyl esters have excellent properties in the formulation of stable food emulsifiers as well as enhanced ability to form complex condensed films at liquid–liquid interfaces, including formulation of cosmetics, herbicides, and drugs. , This, therefore, suggests that the SEFAMESO surfactant ought to be explored beyond the potential use as a cleansing agent to drug formulation, among other applications.…”
Section: Resultsmentioning
confidence: 99%
“…The difference could also be related to varied anionic head group contributions with the sodium sulfonate group in SEFAMESO contributing 11 and sodium sulfate in SDS contributing 38.7 . The HLB value of SEFAMESO suggested that the synthesized surfactant is potentially suitable for use as a wetting or solubilizing agent in the formulation of shampoos. , Studies have also shown that mixed surfactant systems derived from edible oleochemical fatty methyl esters have excellent properties in the formulation of stable food emulsifiers as well as enhanced ability to form complex condensed films at liquid–liquid interfaces, including formulation of cosmetics, herbicides, and drugs. , This, therefore, suggests that the SEFAMESO surfactant ought to be explored beyond the potential use as a cleansing agent to drug formulation, among other applications.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid products (eau de toilettes and perfumes) are directly injected, without sample preparation, except dilution using different solvents or filtration [ 107 , 108 , 109 ] (if the amount of nonvolatile constituents is low when submitted to GC, as the performance of the GC system is rarely hampered by other constituents of the sample). If the analytes occur in more complex media, such as creams, lotions, foundations, and lipsticks, they need to be extracted from their matrix, prior to their analysis, via different established methods: by a fluid (in one step extraction technique [ 110 , 111 , 112 , 113 ] and improved variants such as MSPD: matrix solid-phase dispersion [ 23 , 93 , 114 , 115 ], QuEChERS (quick, easy, cheap, effective, rugged, and safe extraction) [ 116 , 117 , 118 , 119 ], or energy-assisted extraction techniques: vortex-assisted extraction (VAE) [ 120 , 121 ], ultrasound-assisted extraction (UAE) [ 121 , 122 ], and pressurized liquid extraction (PLE) [ 121 , 123 ], by liquid–liquid extraction (LLE) techniques [ 120 , 124 , 125 , 126 , 127 , 128 ], by solid-phase extraction techniques (μSPE: micro solid-phase extraction, dSPE: dispersive solid-phase extraction; SBSE: stir bar sorptive extraction) [ 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ], and gas-phase extraction (headspace solid-phase microextraction (HS-SPME) [ 139 ,…”
Section: Ms Analysis Of Cosmetic Ingredientsmentioning
confidence: 99%
“…Apart from these, many antenna sensors have been designed for air quality monitoring, medical checkup, food analysis, etc. [27][28][29]. However, all these methods are considered to be time-consuming with some complex procedure and complicated data interpretation, which require skilled operators to handle and use these microstripbased antenna sensors.…”
Section: Introductionmentioning
confidence: 99%